A pilot study of motivational interviewing in adolescents with diabetes. Issue 8 (22nd July 2003) - Channon, S; Smith, V J; Gregory, J W
Abstract : Aims: To obtain preliminary data on the impact of motivational interviewing, a counselling approach to behaviour change, on glycaemic control, wellbeing, and self-care of adolescents with diabetes. Methods: Twenty two patients aged 14–18 years participated in motivational interviewing sessions during a six month intervention. The effects of the intervention on HbA1c and a range of psychological factors were assessed. Results: Mean HbA1c decreased from 10.8% to 9.7% during the study and remained significantly lower after the end of the study. Fear of hypoglycaemia was reduced and diabetes was perceived as easier to live with. There were no other significant changes in the psychological measures. By contrast no reduction in HbA1c values was observed in a comparison group who did not receive the motivational interviewing intervention. Conclusion: The findings of this pilot study indicate that motivational interviewing may be a useful intervention in helping adolescents improve their glycaemic control. A larger, longer term randomised controlled study is indicated to clarify the mechanisms and extent of these benefits.